The Effectiveness of Using Electronic Student Worksheet With A Contextual Approach On Student Adversity Quotient - Minadja, Adji W. S.; Sutiarso, Sugeng; Firdaus, Rangga (Universitas Wiralodra, 2024)
This study aims to inspect the effectiveness of using electronic student worksheets with a contextual approach on students' Adversity Quotient (AQ). The research design employed was quasi-experimental. It was conducted at Kotabumi during the academic year 2023/2024, involving 86 VII-th grade students as the population, focusing on the subject matter of social arithmetic. The independent variable in this study is electronic student worksheets with a contextual approach, and the dependent variable refers to the adversity quotient. The research sample was selected using random sampling technique, with 28 students from class VII B assigned to the experimental group and the control group consisted of 28 students from class VII C. The research employed a pre-post control group design. The instrument used was a questionnaire on adversity quotient, which had undergone validity and reliability tests. Data analysis involved descriptive and inferential analyses, with hypothesis testing conducted using independent sample t-tests. Based on the results of the n-gain hypothesis test, there was a difference in the improvement of students' AQ between the experimental and control groups. The findings of this study, as demonstrated through the n-gain test, indicate that the use of electronic student worksheets with a contextual approach is effective in enhancing students AQ.